Infective endocarditis: Awareness, knowledge gaps and behaviours amongst adults with congenital heart disease - S. Haider; K. Krishanthasan; I. Olakorede; A. Constantine; I. Rafiq; K. Dimopoulos (International Journal of Cardiology Congenital Heart Disease)
Background: Adults with congenital heart disease (ACHD) have an increased risk of infective endocarditis (IE), associated with significant morbidity and mortality. This risk is compounded by patient-related factors, including lack of awareness of IE and the presence of a learning disability (LD). Our study sought to evaluate patients' understanding of the risks and symptoms of IE and to identify patients who could benefit from targeted education. Methods: Patients attending the outpatient department of a tertiary ACHD referral centre completed a questionnaire that assessed their knowledge, attitudes and behaviours towards IE. Baseline demographics and clinical data were collected from electronic patient records. Results: A total of 132 ACHD patients completed the questionnaires (age 41.7 ± 16.4 years, 50 % male, 11 % with an LD). Only 37.1 % of patients accurately defined IE, none of whom had an LD. Most patients chose pyrexia (47 %) and tiredness (39.4 %) as potential symptoms of IE, however, none correctly identified all symptoms. Only 19.7 % were aware of the requirement for prolonged antibiotic treatment for IE. A third of all patients reported that they would have made lifestyle changes had they been aware of the complications of IE. There was a statistically significant association between learning disability and poor level of awareness in the questionnaire. Conclusions: Our study demonstrates awareness issues regarding IE among ACHD patients, highlighting the need to invest further on patient education. This should start at the time of transition from paediatric to adult services and continue lifelong, with emphasis on patients with a learning disability.